Examining the Relationship Between Anxiogenic Parenting Practices and Cognitive Flexibility in Youth. Issue 6 (November 2018) - Brennan, Elle; Luke, Anna; Murphy, Yolanda; Francazio, Sarah; Flessner, Christopher
Cognitive flexibility (CF), a subdomain of executive functioning (EF), involves abilities such as set shifting and reversal learning. Some variability in CF is normative across youth due to the gradual refinement of broader EF along with the prefrontal cortex. Prior research has suggested that a supportive parenting environment contributes to strong EF, whereas harsh/controlling parenting is associated with deficits. The current investigation explores whether certain parenting practices (e.g., parental accommodation, over-involvement, modeling) are associated with such deficits. Anxiogenic parenting and CF were assessed in 112 youth aged 9 to 17 years, with results demonstrating that parenting practices were not predictive of CF in these youth. Age accounted for the majority of differences in set shifting performance, potentially emphasizing the influence of parenting at different stages of development. Accordingly, future research is necessary to determine the potential impact of anxiogenic parenting at specific points in the development of CF.